Implementation of Gender Equality Values in Islamic Education Learning to Shape Gender Responsive Behaviour in Students - ANISA DAFA MUTMAINAH; Abu Mansur; Irpinsyah; Hilmy Baihaqi, Mohammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
The purpose of this study is to describe the implementation of gender equality values in Islamic Religious Education (PAI) learning to shape students’ gender-responsive behavior, particularly in class VII, and to identify supporting and inhibiting factors. This qualitative case study collected data through observation, interviews, and documentation, using purposive sampling to select informants. Data were analyzed using the Miles and Huberman model, including data reduction, presentation, and conclusion drawing. The findings reveal that gender equality values are implemented through three strategies: (1) gender-unbiased lesson plans, (2) classroom arrangements that ensure equal access and facilities for all students, and (3) learning methods that promote collaborative interactions without discrimination. Supporting factors include principal support, teacher commitment and awareness, and the content of PAI itself. Inhibiting factors involve the absence of written gender equality policies and the diversity of students’ cultural backgrounds. These findings highlight the importance of structured policies and inclusive practices in fostering gender-responsive behavior in schools.